SECONDARY SCHOOL MATHEMATICS INSTRUCTION ON LINEAR INEQUALITIES IN ONE VARIABLE USING VISUAL APPROACHES - Suhardin
Some mathematical concepts can be presented visually, and this visualization sometimes gives us a deeper understanding. By combining textual mathematics concepts with their visualization, mathematics concepts can be made easier to understand. The 2011 Trends in International Mathematics and Science Study (TIMSS) results showed that many students could not solve linear inequalities problems. The diagnostic test results in this study also show that students experienced difficulties not only with linear inequality concepts but also with algebraic symbol manipulation. These findings lead us to conduct the instruction using visual mathematics. Quantitative and qualitative study are carried out on seventh graders by administering written tests before and post the instruction process, followed by interviews. The sample population consisted of twenty students working on the written tests, and five of them were interviewed afterward. The findings show that the instructions using visual mathematics improve the test scores.